Men's Bodily Attractiveness: Muscles as Fitness Indicators. (3rd June 2019) - Durkee, Patrick K.; Polo, Pablo; Muñoz-Reyes, José Antonio; Rodríguez-Ruiz, Claudia; Losada-Pérez, María; Fernández-Martínez, Ana B.; Turiégano, Enrique; Buss, David M.; Pita, Miguel
Bodily attractiveness is an important component of mate value. Musculature—a crucial component of men's bodily attractiveness—provides women with probabilistic information regarding a potential mate's quality. Overall musculature is comprised of several muscle groups, each of which varies in information value; different muscles should be weighted differently by attractiveness-assessment adaptations as a result. In the current study, women and men ( N = 1, 742) reported size preferences for 14 major muscle groups. Women's reported preferences provided only partial support for our hypotheses that women will prefer muscles that most reliably differentiate between potential mates to be larger; men tended to prefer larger upper-body muscles. We discuss possible interpretations of these mixed findings. Ultimately, our findings suggest that attractiveness-assessment adaptations are sensitive to the information contained within specific muscle groups and they highlight the potential for additional research on the nuances of bodily attractiveness assessment.